Impact of a medical mobile phone app (QUiPP) for predicting preterm birth on the anxiety and decisional conflicts faced by women in threatened preterm labour. (January 2021) - Carlisle, N.; Watson, H.A.; Seed, P.T.; Carter, J.; Kuhrt, K.; Tribe, R.M.; Shennan, A.H.
Highlights: QUiPP is a validated phone application that supports clinical decision-making for preterm labour Seeing a clinician has a positive effect on reducing anxiety in women in threatened preterm labour The QUiPP app has potential to reduce anxiety and decisional conflict in women Appears to be a divide between a clinician's priorities and women's motivations for seeking help Abstract: Background: The QUiPP app is a free, validated mobile phone application (app) that supports clinical decision-making for women in threatened preterm labour by providing an individualised risk of delivery within clinically important time points. Alongside generating a percentage risk score, the QUiPP app also provides the risk score in an infographic donut chart, allowing the clinician to communicate with the woman in an easy to understand format. Informing women of their risk status using the QUIPP app may help to reduce anxiety in women and decrease decisional conflict. Method: A subset of participants from the EQUIPTT study [REC Ref. 17/LO/1802] were asked to complete a questionnaire booklet which was used to evaluate decisional conflict and anxiety. Seven sites were randomised to the QUiPP app intervention (to use as a decision and communication tool) and six sites were randomised to the control (continued their normal practice). The first section of the questionnaire booklet was completed by the woman before her assessment, and the second section after. The pre and postassessment anxiety scores utilised the Visual Analogue Scale for Anxiety (Hornblow and Kidson, 1976). The Decisional Conflict Scale (O'Connor, 1995) measured decisional conflict post assessment. The data were then analysed to determine the impact of the QUiPP App on the anxiety and decisional conflicts faced by women in threatened preterm labour. Results: Questionnaires were completed by 221 women from 12 of the potential 13 sites. After exclusions 202 questionnaires were included in the analysis. There was a significant reduction in difference between anxiety scores before and after clinical assessment. While there were reductions in anxiety and decisional conflict for women who were aware of the QUiPP app use, this failed to reach statistical significance. Conclusions: The QUiPP app has potential to reduce anxiety and decisional conflict in women who are aware that it is being used in their care. Additional work is required to ensure clinicians are aware of the QUiPP app and optimise using it as a communication tool when counselling women.